PENERAPAN HUKUM KELUARGA ISLAM DALAM MENJAGA KEHARMONISAN RUMAH TANGGA HASIL PROSES TA’ARUF (Studi Kasus di Desa Kalikejambon Kecamatan Tembelang Kabupaten Jombang) - Iklima Amanatuz zakiyyah; M. Syam’un Rosyadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The phenomenon of ta'aruf as a premarital introduction method aligned with Islamic law principles has emerged as a contemporary discourse and an ideal paradigm among the millennial generation to foster harmonious domestic structures. Within the community of Kalikejambon Village, this instrument is perceived as highly effective in supporting the establishment of a resilient family institution. This study is oriented to thoroughly investigate the procedural execution of ta'aruf and analyze the application of Islamic family law in sustaining marital resilience after the solemnization of marriage. The scholarly novelty of this research lies in its comprehensive integrative analysis, which linearly correlates the premarital acquaintance phase with the success of constructing domestic harmony. Methodologically, this inquiry is designed as an empirical field study adopting a qualitative approach, subsequently elaborated through a descriptive-analytical framework. The selection of Kalikejambon Village in Jombang Regency as the research site is predicated on the significant presence of couples who underwent this process prior to solemnizing their official marriage. Primary data structures were gathered through in-depth interview techniques with practicing couples and local community leaders. Concurrently, secondary data were compiled by exploring a rich body of literature, including religious texts, marriage legislation, academic theses, copies of judicial decisions, and relevant contemporary scholarly journals. The socio-legal findings of this research indicate several primary determinants driving the community to opt for this path, including sociological environmental influences, a profound commitment to consistently practice Islamic law, and the explicit rejection of conventional dating culture. Furthermore, the continuity of marital stability is nurtured through the internalisation of mutualistic values, such as mutual respect, the cultivation of trust, the reinforcement of interpersonal communication patterns, and the fulfillment of primary and secondary material necessities. Additionally, active collective engagement in various community activities at the local village level significantly reinforces their marital endurance.